Effect of sulfuric acid addition on the yield and composition of lignin derived oligomers obtained by the auger and fast pyrolysis of Douglas-fir wood - Zhou, S.; Osman, N.; Li, H.; McDonald, A.; Mourant, Daniel; Li, Chun-Zhu; Garcia-Perez, M. (Elsevier Science Ltd, 2013)
This paper investigates the effect of sulfuric acid (H2SO4) concentration, as an additive to enhance theproduction of anhydrosugars via pyrolysis of Douglas-fir, on the yield and composition of the ligninderived oligomers. Pyrolysis tests at 500 C were conducted in auger and fluidized bed reactors. For both reactors the yield of lignin derived oligomers decreased as H2SO4 was added. Several analytical techniques (UV-fluorescence, TGA, ESI-MS, FTIR, solid state 13C NMR and Pyrolysis-GC/MS) were used to characterize the lignin derived oligomers collected. Four peaks were observed in the UV-fluorescence spectra. The addition of H2SO4 reduces the yield of all the peaks. DTG curves also show the presence of several peaks. The addition of H2SO4 decreased the yield of all the peaks but its effect was more pronounced on peaks at 320 and 400 C. Electrospray ionization-mass spectrometry studies did not show any major change on the molecular weight of the lignin oligomers ionized products obtained as a function of H2SO4 concentration. Solid state NMR results indicate that the methoxyl groups decreased and the carbonyl increased gradually as sulfuric acid concentration increases. The Py-GC/MS confirmed the phenolic compounds with methoxyl substitutions were substantially reduced as the acid concentration increased. The experimental results obtained suggest the presence of H2SO4 enhances the polycondensation of methoxyl substituted aromatic rings.